10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
Microglia are the major resident immune cells in the central nervous system (CNS). They emerge at very early stages of brain development and subsequently expand and persist through self-renewal within the CNS. As a result, microglial behaviors are profoundly shaped by the CNS microenvironment, enabling them to meet the unique demands of neural tissue and to cope with CNS stresses. Neurotransmitters are the primary chemical messages that are conveyed between neurons; however, glia cells, including microglia, are now known to express a wide array of neurotransmitter receptors as well. This positions neurotransmitters as a fundamental mode of communication among most CNS cells. Despite this, the significance of neurotransmitter signaling in microglia biology and function remains elusive. Research studies have begun to unravel the repertoire of neurotransmitter receptors expressed by microglia, the signaling pathways they engage, and the consequences for brain physiology and pathology. These advances have raised new questions and marked the beginning of a new era in neuron-microglia research. In this review, we summarize the latest discoveries concerning neurotransmitter receptors in microglial biology and CNS diseases, and we also discuss future perspectives, including potential clinical applications.